The Separating Technique of Abalone (Haliotis squamata) at Marine Aquaculture Development Centre (MADC) Lombok, West Nusa Tenggara Province - arif habib fasya; Mohammad Faizal Ulkhaq; Ade Prasetyo Abdi (Airlangga University, 2021)
The purpose of this research is to find out the abalone separating technique (H. squamata) and know the problems during separating at the Marine Aquaculture Development Centre, West Nusa Tenggara Province. Research are carried out on December 23, 2019 to January 21, 2020. The method used is descriptive method with data collection including primary data and secondary data. Data is taken by observing, active participation, interviewing, and literature review. Abalone separating techniques (H. squamata) begin with container preparation, seed preparation, seed stocking, seeding, feeding, water quality management, and growth sampling. Problems encountered during the separating stage are the uncertain availability of seaweed feed. Keyword : Abalone, H. squamata, separating technique.